1995
DOI: 10.1093/carcin/16.11.2751
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibre characteristics on cytotoxicity and induction of anaphase/telophase aberrations in rat pleural mesothelial cells in vitro: correlations with in vivo animal findings

Abstract: Thirteen samples of natural fibres and five samples of man-made fibres (MMF) were tested to determine their cytotoxicity and ability to produce chromosome missegregation in cultures in rat pleural mesothelial cells (RPMC). The natural samples included attapulgite, two amphiboles (amosite and crocidolite); seven consisted of chrysotile from various origins and three were obtained after chemical treatment of chrysotile. MMF included three refractory ceramic fibres (RCF) and two vitreous fibres (MMVF). All fibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…Centrosome fragmentation, mitotic spindle disruption, and aneuploidy are characteristics of cancer cells and may lead to an increased risk of cancer [23,25]. Consistent with this hypothesis, research with inorganic fibers indicate that in vivo asbestos-induced mesothelioma is correlated with the ability of the fiber to cause chromosomal missegregation, not with cytotoxicity [81]. The current research demonstrating mitotic spindle disruption and errors in chromosome number indicates caution should be used during the production and processing of carbon nanotubes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Centrosome fragmentation, mitotic spindle disruption, and aneuploidy are characteristics of cancer cells and may lead to an increased risk of cancer [23,25]. Consistent with this hypothesis, research with inorganic fibers indicate that in vivo asbestos-induced mesothelioma is correlated with the ability of the fiber to cause chromosomal missegregation, not with cytotoxicity [81]. The current research demonstrating mitotic spindle disruption and errors in chromosome number indicates caution should be used during the production and processing of carbon nanotubes.…”
Section: Discussionsupporting
confidence: 55%
“…Mitotic spindle damage with a predominantly multipolar phenotype and aneuploidy have also been observed following in vitro treatment with 0.25 μg/mL of the potent occupational carcinogen, chrysotile asbestos [80]. The ability of asbestos fibers to induce aneuploidy in vitro is highly correlated with the ability to induce mesotheliomas in vivo; this provides data supporting the importance of aneuploidy in carcinogenesis due to particulates with high aspect ratios [81]. Chrysotile has also been observed to cause a G2/M block similar to the block observed with SWCNT [48].…”
Section: Discussionmentioning
confidence: 73%
“…The formation of abnormal anaphases was not dependent on the presence of antioxidant enzymes (103). The physical presence of fibers in dividing cells seems a more likely mechanism by which fibers impair mitosis.…”
Section: Mechanisms Of Chromosome Damagementioning
confidence: 86%
“…Pelin et al (102) found that chrysotile and crocidolite produced a significant enhancement of the percentage of abnormal anaphases in HMC treated with chrysotile and crocidolite, but amosite produced only a slight increase. Similarly, Yegles et al (103) observed that crocidolite and several samples of chrysotile produced a significant number of abnormal anaphases, but amosite and MMMF [refractory ceramic fibers (RCFs), MMVF] were inactive. The authors suggest that the absence of effect from some fiber types may be due to an insufficient number of relevant fibers.…”
Section: Chromosome Damagementioning
confidence: 93%
See 1 more Smart Citation